THE INFLUENCE OF CEO EDUCATION ON AUDIT FEES WITH AUDIT COMMITTEE EXPERIENCE AS A MODERATION VARIABLE - Riska Widya Pangestika; Samsul Rosadi (P3I UMSurabaya, 2024)
This research aims to investigate the impact of CEO education on audit fees, measured using the natural logarithm, and its interaction with audit committee experience. The study also explores the influence of CEO education on audit fees, considering the moderating effect of audit committee experience. The relationships between independent variables, dependent variables, and moderating variables are analyzed through regression analysis. Panel data from IDX property and real estate companies spanning 2018–2023 are utilized. Findings indicate that CEO education, assessed by scores, negatively affects audit fees. However, CEO economic background positively influences audit fees, and CEO education moderated by audit committee experience has a negative impact. Consequently, educating both the CEO and audit committee is recommended to mitigate company risk and decrease audit costs.